Structure and emission properties of dinuclear copper(i) complexes with pyridyltriazole. Issue 6 (27th January 2023) - Gusev, Alexey; Kiskin, Mikhail; Braga, Elena; Zamnius, Ekaterina; Kryukova, Mariya; Karaush-Karmazin, Nataliya; Baryshnikov, Glib; Minaev, Boris; Linert, Wolfgang
Abstract : New highly emissive copper(i ) complexes based on 3/4-pyridyltriazole have been synthesized and fully characterized. Photophysical properties and the mechanism of photo- and mechanochromic and excitation dependent luminescence are discussed. Abstract : A new series of five highly emissive binuclear heteroleptic pyridyltriazole-Cu(i )-phosphine complexes 1–5 was synthesized and examined by different experimental (IR, elemental and thermogravimetric analysis, single crystal X-ray diffraction technique, UV-vis and fluorescence spectroscopy) and quantum chemical aproaches. Complexes 1–5 exhibited excellent stimuli-responsive photoluminescent performance in the solid state at room temperature (quantum yield (QY) = 27.5–52.0%; lifetime ( τ ) = 8.3–10.7 μs) and when the temperature was lowered to 77 K (QY = 38.3–88.2; τ = 17.8–134.7 μs). The highest QY was examined for complex 3 (52%) that can be explained by the small structural changes between the ground S0 and exited S1 and T1 states leading to the small S1 –T1 triplet gap and efficient thermally-activated delayed fluorescence. Moreover, complex 4 demonstrates reversible mechanochromic and excitation dependent luminescence.